2017
DOI: 10.1007/s12288-017-0808-x
|View full text |Cite
|
Sign up to set email alerts
|

Pantoprazole Induces Apoptosis of Leukemic Cells by Inhibiting Expression of P-Glycoprotein/Multidrug Resistance-Associated Protein-1 Through PI3K/AKT/mTOR Signaling

Abstract: This study aims to investigate the effects and mechanism of pantoprazole on multidrug resistant leukemia K562/A02 and K562/ADM cell lines. K562/A02 and K562/ADM cells at logarithmic growth phase were pre-treated with different concentration of pantoprazole (0, 50, 100, 200 μg/mL) for 24 h. Flow cytometry was used to measure the cell growth cycle and apoptosis. RT-PCR and Western blot were used to measure the expression of p-PI3K, p-AKT, p-mTOR, P-glycoprotein (P-gp) and multidrug resistance-associated protein-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The same applies for rofecoxib (Figure ), which showed to downregulate mRNA and protein levels of MRP1, but also GST, at a concentration of 10 μM using BGC‐823 gastric cancer cells . Here, it is worth to mention that downregulation of MRP1 transcript and protein has also been observed for other pharmacological and experimental drugs, such as fidarestat, LSS‐11, pantoprazole, and U0126 (Figure ) …”
Section: Pharmacological and Experimental Drugs And Synthetic Analogssupporting
confidence: 55%
“…The same applies for rofecoxib (Figure ), which showed to downregulate mRNA and protein levels of MRP1, but also GST, at a concentration of 10 μM using BGC‐823 gastric cancer cells . Here, it is worth to mention that downregulation of MRP1 transcript and protein has also been observed for other pharmacological and experimental drugs, such as fidarestat, LSS‐11, pantoprazole, and U0126 (Figure ) …”
Section: Pharmacological and Experimental Drugs And Synthetic Analogssupporting
confidence: 55%
“…The mRNA and protein levels of Survivin and P-gp in MCF-7/DOX cells were also significantly higher than that in the normal cells, which indicated that the drug resistance of MCF-7/DOX cells was closely related to the high expression of Survivin and P-gp. Several anticancer drugs (e.g., Pantoprazole ( Liu et al, 2017 ), Tanshinone-1 ( Xu et al, 2013 ), Resveratrol ( Wang L. et al, 2016 ), Ubenimex ( Guo et al, 2019 )) could down-regulate the expression of P-gp through the PI3K/Akt/mTOR pathway, thereby enhancing the anticancer effect of chemotherapy drugs ( Liu et al, 2014 ; Han et al, 2016 ; Chi et al, 2017 ). Similarly, our results confirmed that Survivin might affect the PI3K/Akt/mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway also played an essential role in promoting cell growth, proliferation, metastasis, and chemotherapy resistance ( Khan et al, 2013 ; Ahmad et al, 2020 ; Liu et al, 2020 ). It was reported that the P-gp-encoding gene MDR1 was regulated by mTOR ( Liu et al, 2017 ). Blocking PI3K/Akt/mTOR pathway with the specific inhibitor (LY294002) could reduce the basal level of P-gp and antagonize multi-drug resistance ( Wang C. et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Preclinically, PPIs have shown substantial anticancer, chemosensitizing and radiosensitizing activities that extend beyond gastric and esophageal cancers. Some of the cancer types that showed promising effect upon the addition of PPIs include pancreatic (97), colorectal (27,98), ovarian (99), prostate (100), breast (101, 102), lung (56), melanoma (103), lymphoma (104), myeloma (105), osteosarcoma (106) and leukemia (107). This broad anticancer activity of PPIs is likely related to the pleotropic effect of the drug targeting cancer cell growth-, metastasis-, and autophagy-related gene networks (4).…”
Section: Repurposing Ppis For Cancer Carementioning
confidence: 99%